Human Dimensions of the Reintroduction of Brazilian Birds - Martins, Flávia de Campos; Engel, Mônica T.; Schulz, Francine; Martins, Cláudia S. G. (Frontiers in Conservation Science, 2022)
People's acceptability for wildlife, stakeholders' engagement and involvement are acknowledged as key factors for the success of wildlife reintroduction projects. We analyzed the main National Action Plans (NAPs) (the Brazilian management participatory instrument for the conservation of endangered species) for eight bird species and conducted an online questionnaire with researchers and practitioners involved in those species reintroduction programs. The assessment of the main Brazilian bird's reintroduction programs showed that, in general, efforts have been made to integrate local people into it. Nevertheless, the actions were disconnected, isolated and fragmented. A formal protocol, designed, discussed and approved by experts aiming to address the human dimensions (HD) of human-bird interactions (HBI), preferably to be used in each stage of the reintroduction programs, was not found. Actions considered related to human dimensions are mainly under the umbrella of environmental education interventions or campaigns, more directed to children and youth; correspond to activities performed by locals with the birds and/or captive birds facilities; or, fostering artcraft production or bird watching activities. The weak or sometimes absent human dimensions approach to this important conservation tool may indicate either the novelty for Brazilian researchers and managers of the science of human dimensions within the field of wildlife management or the lack of dialogue between natural and social sciences when wildlife conservation is at stake. Reintroductions are expensive, sensitive, and labor-intensive processes. It becomes necessary due the conservation status of the species and its implementation follows a careful research of biological, ecological and socio-institutional regional background that identifies the drivers of species extinction and plans according to it. Understanding and predicting people's behaviors and its triggers are paramount to successful reintroduction projects. Thus, making use of well-planned HD studies in HBI may be the watershed between success or failure of reintroduction programs. This study was a pioneer initiative of its kind and it aimed to provide sound recommendations for managers, researchers and practitioners to acknowledge the relevance of HD and its core role in the reintroduction of endangered bird species.